Common Fixed Points for Multivalued Mappings in Complex Valued Metric Spaces with Applications. (26th December 2013) - Ahmad, Jamshaid; Klin-Eam, Chakkrid; Azam, Akbar
Abstract : In this paper, we introduce the notion of multivalued contractive mappings in complex valued metric space and prove common fixed point theorems for two multivalued contractive mappings in complex valued metric spaces without using the notion of continuity. Our results improve and extend the results of Azam et al. (2011).